Synthesis and characterization of SiO2 from Madura Strait sediment with leaching acid treatment - Hidayat, Arif; Wijaya, Anugrah Ricky; Kusumaningrum, Irma Kartika (Eclética Química, 2026)
Silicon dioxide (SiO₂) was successfully synthesized from Madura Strait sediment. The production process involved a wet digestion step using a strong acid to decompose the sample. Subsequent calcination and purification with strong acid effectively removed impurities, yielding a white sedimentary material. The synthesized SiO₂ was characterized using X-ray fluorescence (XRF), X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), and scanning electron microscopy (SEM). After impurity removal, the silicon content in the raw sediment increased from 33.5% to 83.3%. XRD analysis confirmed the successful formation of amorphous SiO₂ particles. FTIR spectra indicated the presence of Si–O–Si and Si–OH functional groups, representing silanol and siloxane structures. SEM analysis revealed that the SiO₂ particles formed aggregates with an irregular arrangement, where individual particles appeared loosely associated.